Prevalence of disability and associated factors in Dabat Health and Demographic Surveillance System site, northwest Ethiopia - Mulugeta Bayisa Chala; Solomon Mekonnen; Gashaw Andargie; Yigzaw Kebede; Mezgebu Yitayal; Kassahun Alemu; Tadesse Awoke; Mamo Wubeshet; Temesgen Azmeraw; Melkamu Birku; Amare Tariku; Abebaw Gebeyehu; et al. (BMC, 2017)
Abstract Background Despite the high burden of disability in Ethiopia, little is known about it, particularly in the study area. Hence, this study aimed to investigate the prevalence and factors associated with disability at Dabat Health and Demographic Surveillance System (HDSS) site, northwest Ethiopia. Method A population-based study was conducted from October to December 2014 at Dabat HDSS site. A total of 67,395 people were included in the study. The multivariable binary logistic regression analysis was employed to identify factors associated with disability. The Adjusted Odds Ratio (AOR) with a 95% Confidence Interval (CI) was estimated to show the strength of association. A p-value of <0.05 was used to declare statistical significance. Results One thousand two hundred twenty-eight individuals were reported to have a disability giving a prevalence rate of 1.82%, of which, about 39% was related to a vision disability. The high odds of disability were observed among the elderly (≥50 years) [AOR: 4.49; 95% CI: 1.95, 10.33], severely food in-secured [AOR: 2.11; 95% CI: 1.59, 2.80], and separated marital status [AOR: 7.52; 95% CI: 1.18, 47.84]. While having a paid job [AOR: 0.46; 95% CI: 0.28, 0.77], being in the richest quintile [AOR: 0.55; 95% CI: 0.41, 0.75], and high engagement in work-related physical activities [AOR: 0.36; 95% CI: 0.27, 0.49] were inversely associated with the disability. Conclusion Disability is a major public health problem, and the burden is noticeable in the study area. Vision disability is the highest of all disabilities. Thus, efforts must be made on educating the public about disability and injury prevention. Measures that reduce disability should target the elderly, the poorer and the unemployed segment of the population.